Induksi Tunas Kunyit Putih (Curcuma zedoaria Roscoe) Pada Media MS Dengan Penambahan Berbagai Konsentrasi BAP dan Sukrosa Secara In Vitro - Dola Ratna Yulizar; Zozy Aneloi Noli; M Idris (Universitas Andalas, 2014)
Murashige-Skoog media enriched using 6-Benzyl Aminopurine (BAP) and sucrose was conducted from June 2013 to February 2014 at the Laboratory of Plant Physiology, Department of Biology, Andalas University. This study aimed to determine the ability of shoot formation of white turmeric (Curcuma zedaoria Roscoe) on the effect of BAP and sucrose concentration. We used a Completely Randomized Design (CRD) with 8 treatments and 3 replications, BAP (0, 1.5, 3 and 4.5 mg/L) and sucrose (3 and 5%) of MS medium. The result showed that the percentage of shoot induction was 100%. The best combination of sucrose and BAP in shoot induction was obtained on 5% sucrose and 1.5 mg/L BAP. While for the first immerge of shoot was obtained on 5% sucrose and 4.5 mg/L BAP in 5 days after inoculation. All treatments but did not give any significant effect to the number and height of shoots.Key words: Curcuma zedoaria, shoot, sucrose and 6-Benzyl Aminopurine